Optimalizace vybraných inženýrských úloh - Přikryl, Tomáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Cílem této práce je pochopení základních pojmů z oblasti matematického programování a jejich aplikace na optimalizaci strojního návrhu. Hlouběji je zkoumáno odvětví nelineární optimalizace a metod řešení nelineárních optimalizačních úloh. Práce také obsahuje nezbytné poznatky o strojí- renské součásti hřídeli. V praktické části jsou tyto poznatky aplikovány na návrh optimální hřídele z hlediska hmotnosti.

The goal of this paper is a basic understanding of elementary concepts of the mathematical programming field and an aplication of such concepts for the optimization of machine design. The subject of nonlinear optimization is put under deeper scrutiny and so are solution methods of nonlinear problems. This paper also contains essential findings about shafts in the context of engineering components. In the practical part these findings are applied for an optimization of a shaft where the goal is to minimize the shaft’s weight.
Optimization in selected engineering problems
Keywords: Matematické programování; nelineární optimalizace; hřídel; Mathematical programming; nonlinear optimization; shaft